Viability of fair price ships: role of macro-level factors - Kabra, Kamal Nayan
It is often maintained that the public distribution system (PDS) tends to become weak at the cutting edge level on account of many operational problems. One such factor often highlighted is the inadequacy of legal returns and income obtained by the fair price shop (FPS) owner. This issue is generally examined in terms of the costs and returns available to the FPS dealer. In this paper, it is maintained that the basic constraint on the viability of FPS arises from the fact that there is a disproportion between the number of FPS needed and set up in the country, and the total off take or supplies from the PDS. It is this factor which blocks attempts to ensure the viability of the FPS system. Reproduce
Keywords: Public Distribution System; India; Fair Price Shop; Public Distribution System - India